Research progress on the role of lncRNA–miRNA networks in regulating adipogenic and osteogenic differentiation of bone marrow mesenchymal stem cells in osteoporosis - An, Fangyu; Wang, Xiaxia; Wang, Chunmei; Liu, Ying; Sun, Bai; Zhang, Jie; Gao, Peng; Yan, Chunlu (Frontiers in Endocrinology, 2023)
Osteoporosis (OP) is characterized by a decrease in osteoblasts and an increase in adipocytes in the bone marrow compartment, alongside abnormal bone/fat differentiation, which ultimately results in imbalanced bone homeostasis. Bone marrow mesenchymal stem cells (BMSCs) can differentiate into osteoblasts and adipocytes to maintain bone homeostasis. Several studies have shown that lncRNAs are competitive endogenous RNAs that form a lncRNA-miRNA network by targeting miRNA for the regulation of bone/fat differentiation in BMSCs; this mechanism is closely related to the corresponding treatment of OP and is important in the development of novel OP-targeted therapies. However, by reviewing the current literature, it became clear that there are limited summaries discussing the effects of the lncRNA-miRNA network on osteogenic/adipogenic differentiation in BMSCs. Therefore, this article provides a review of the current literature to explore the impact of the lncRNA-miRNA network on the osteogenic/adipogenic differentiation of BMSCs, with the aim of providing a new theoretical basis for the treatment of OP.